Learning Dance to Improve Motor Skills of Lightweight Palsy Cerebral Patients at YPAC Semarang - Rimasari Pramesti Putri; Bintang Hanggoro Putro (Jurnal Pendidikan Indonesia, 2021)
The National Education System Law Number 20 of 2003 states, "Special education is a form of education that specifically serves children who have visual, hearing, intellectual, physical or emotional barriers". The purpose of this paper is to apply dance learning as a medium for motor physical therapy for mild cerebral palsy sufferers at YPAC Semarang. This research method study uses a descriptive qualitative approach where the researcher observes the implementation of dance learning and presents the data in the form of data description, analysis, and interpretation. The result of this research is that learning dance can improve motor skills of patients with Cerebral Palsy light at YPAC Semarang. This increase in motor skills includes reduced stiffness when moving. In addition to motor skills, learning to dance to sufferers. The results of this study can be concluded that Cerebral Palsy can improve children's ability to manage emotions, improve problematic behavior, increase concentration, and increase self-confidence.